PLGA Nanoparticles Co-encapsulating NY-ESO-1 Peptides and IMM60 Induce Robust CD8 and CD4 T Cell and B Cell Responses - Dölen, Yusuf; Gileadi, Uzi; Chen, Ji-Li; Valente, Michael; Creemers, Jeroen H. A.; Van Dinther, Eric A. W.; van Riessen, N. Koen; Jäger, Eliezer; Hruby, Martin; Cerundolo, Vincenzo; Diken, Mustafa; Figdor, Carl G.; et al. (Frontiers in Immunology, 2021)
Tumor-specific neoantigens can be highly immunogenic, but their identification for each patient and the production of personalized cancer vaccines can be time-consuming and prohibitively expensive. In contrast, tumor-associated antigens are widely expressed and suitable as an off the shelf immunotherapy. Here, we developed a PLGA-based nanoparticle vaccine that contains both the immunogenic cancer germline antigen NY-ESO-1 and an α-GalCer analog IMM60, as a novel iNKT cell agonist and dendritic cell transactivator. Three peptide sequences (85-111, 117-143, and 157-165) derived from immunodominant regions of NY-ESO-1 were selected. These peptides have a wide HLA coverage and were efficiently processed and presented by dendritic cells via various HLA subtypes. Co-delivery of IMM60 enhanced CD4 and CD8 T cell responses and antibody levels against NY-ESO-1 in vivo. Moreover, the nanoparticles have negligible systemic toxicity in high doses, and they could be produced according to GMP guidelines. Together, we demonstrated the feasibility of producing a PLGA-based nanovaccine containing immunogenic peptides and an iNKT cell agonist, that is activating DCs to induce antigen-specific T cell responses.